ANALISIS YURIDIS TERHADAP KEWAJIBAN TANGGUNG JAWAB SOSIAL PERUSAHAANPENANAMAN MODAL ASING YANG BERUBAH MENJADI BADANUSAHA MILIK NEGARA (PERSERO) (STUDIPADA PT. INDONESIA ASAHANALUMINIUM) - M. RASYID RIDHA (PREMISE LAW JURNAL, 2017)
ABSTRACT The difference in the regulation on CSR between PMA companies and BUMN is stipulated in Article 74, paragraph 1 which states that a corporation which operates in natural resources has to carry out Corporate Social Responsibility. Law No. 25/2007 on Capital Investment and Article 88 of Law No. 19/2003 on BUMN state that a BUMN can set its part of profit aside for fostering small businesses/cooperatives and the people surrounding it, in conjunction with the Decree of the Minister of State for BUMN No. PER-09/MBU/07/2015 on Partnership Program and Environmental Development Program of BUMN. Article 88 can also be identified as CSR although its term is “fostering small businesses/cooperatives and the people surrounding BUMN.” This article further explains the Decree of the Minister of State for BUMN No. PER-09/MBU/07/2015 on Partnership Program and Environmental Development Program of BUMN in which Partnership Program and Environmental Development Program have to be carried out by Perum or Persero. Keywords: Corporate Social Responsibility of Foreign Investment Company,Change to BUMN